1999
DOI: 10.1192/bjp.174.4.322
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural comparison of depressive symptoms in Europe does not support stereotypes of ageing

Abstract: Variations in the prevalence of depressive symptoms occurred between centres, not always related to levels of illness. There was no consistent relationship between proportions of symptoms in well persons and cases for all centres. Few symptoms were present in > 60% of the older population--stereotypes of old age were not upheld.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 7 publications
4
10
0
Order By: Relevance
“…We found the longer the marriage was, the more men undergoing IUI were prone to suffer from depression. The financial burdens of treatment were the most severe risk factor associated with depression (approximately a 3.58-fold increased risk), and the current findings were in agreement with data from other studies [25][26][27][28]. Fortunately, psychological treatment could decrease depression scores among low-income infertile couples [29].…”
Section: Discussionsupporting
confidence: 91%
“…We found the longer the marriage was, the more men undergoing IUI were prone to suffer from depression. The financial burdens of treatment were the most severe risk factor associated with depression (approximately a 3.58-fold increased risk), and the current findings were in agreement with data from other studies [25][26][27][28]. Fortunately, psychological treatment could decrease depression scores among low-income infertile couples [29].…”
Section: Discussionsupporting
confidence: 91%
“…Similarly to most reports, depressive conditions in ZARADEMP 0 were higher in women when compared to men (Weissman and Klerman 1985), and also in lower educational levels (Weissman et al 1991, Lobo et al 1995. Furthermore, we reported during the same investigation wide differences of prevalence of both, depression and depressive symptoms between our city and other European cities (Copeland et al 1999b, Copeland et al 1999c, and the influence of social and environmental factors was suggested. By itself, however, this association does not reveal a causal connection, since social problems have also been reported as a consequence of depression (Van Hook 2003).…”
Section: New Inquiries Into the Epidemiology Of Depression In The Eldsupporting
confidence: 86%
“…Finally, the ZARADEMP Project was designed to compare incidence rates of dementia, as well as depression, and risk factors for both conditions found in Zaragoza with data reported using the same methods in other European cities during the EURODEM (Launer et al 1992b) and EURODEP (Copeland et al 1999b) studies respectively. Differences found in prevalence rates of both dementia (Lobo et al 2000) and depression (Copeland et al 1999c) in these previous reports, which include preliminary data from Zaragoza, are encouraging, since substantial epidemiological reasoning would be prompted if crossnational differences are confirmed. However, prevalence studies may be influenced by duration and fatality rates.…”
Section: Other Objectives Of the Project: Cross-cultural Comparisonsmentioning
confidence: 63%
“…In another model, we left out the item on interest, as the loss of interest is not necessarily an indicator for depression, especially at older ages. Following the idea of Copeland et al (1999a) we left out the somatic symptoms when calculating the level of depression in the third model. The analysis clearly shows that our results are stable and do not depend on the 12 contributing items (tables not shown here).…”
Section: Multivariate Resultsmentioning
confidence: 99%